KEEFEKTIFAN MODEL PEMBELAJARAN AIR (AUDITORY INTELLECTUALLY REPETITION) TERHADAP HASIL BELAJAR TEMA 6 SISWA KELAS V - Susilo Bayu Mustofa; Ika Listyarini; Mei Fita Asri Untari (FKIP, PGSD, Universitas Slamet Riyadi, 2020)
This study aims to determine the effectiveness of the Auditory Intellectualy Repetition (AIR) learning model on the learning outcomes of the theme of 6th grade students of SDN Bumiharjo 02 Pati Regency. This type of research is quantitative in the form of Pre Experimental Design, with the design of One Group Pretest Posttest Design. In this study using a sampling technique that is saturated all students in grade V. Data collection techniques used were interviews, tests, observations, and documentation. Learning outcomes in the study are the pretest value of 59.869565 and with an increase in the average posttest value of 84.347826. T Test results obtained tcount more than ttable (0.173> 0.104) then H0 is rejected and Ha is accepted. So, the conclusion is that the Auditory, Intellectually, Repetition (AIR) learning model is effective on the learning outcomes of the theme of the 6th grade students of SDN Bumiharjo 02 Pati Regency.